Diachronous sub‐volcanic intrusion along deep‐water margins: insights from the Irish Rockall Basin. (February 2014) - Magee, C.; Jackson, C. A.‐L.; Schofield, N.
Abstract The movement of magma in sedimentary basins often occurs through an extensive and interconnected complex of sills. Field‐, modelling‐, and seismic reflection‐based studies indicate that the emplacement of shallow‐level sills is commonly accommodated by the formation of forced folds, which may be expressed at the free surface and onlapped by younger strata. If the age of these onlapping strata can be constrained, important insights can be gained into the timing of magma emplacement and associated regional, tectono‐magmatic events. Previous studies have focused on isolated intrusions that are overlain by an individual forced fold formed during a single tectono‐magmatic event. However, the structure and evolution of 'compound' folds developed above stacked, interconnected sills, and what they may reveal about polyphase intrusive events has not been investigated. In this study, we use 3D seismic reflection data from the Irish Rockall Basin, offshore western Ireland, to constrain the structural style and emplacement history of a sill complex that contains 82 seismically resolved intrusions. Individual forced folds, <41 km2 in plan view and with mean fold amplitudes of 111 m, are developed above single intrusions. However, where sills are stacked, broader (100–244 km2), larger amplitude (mean of 296 m) compound folds occur following the coalescence of individual folds. Stratigraphic onlap and truncation observed within the folds throughout the Palaeocene‐to‐Middle Eocene succession, indicates that emplacement and forced folding initiated at the end Maastrichtian and lasted for ca. 15 Ma, before ceasing near the end of the Ypresian. We demonstrate (i) intrusion‐induced forced folds evolve dynamically and can form broad areas of sustained local uplift, and (ii) that the formation of sill complexes within the upper crust may occur over prolonged time periods. This study also highlights the importance of seismic reflection data to understanding the structural style and age relationships between igneous systems.